Bowen's disease in the eye - Natteri R., Américo (1957)
In 1942, McGavic, Institute of Ophthalmology of Presbyterian Hospital, published five cases of tumors affecting the connective-corneol that area and histological features were similar to the entity in 1912, Bowen describe skin dermatoses Pre- cancer, with the title "A study of two cases gives Atypical Epithelial Proliferation".